Redefining the Way Theatre is Created and Performed: The Radical Inclusion of Suzan-Lori Parks's 365 Days/365 Plays - Kolin, Philip C. (Journal of Dramatic Theory and Criticism, 2007)
Redefining the Way Theatre is Created and Performed: The Radical Inclusion of Suzan-Lori Parks's 365 Days/365 Plays